From participation to commitment in silvopastoral programmes: Insights from Chiapas, Mexico - Zabala, Aiora; Barrios, Luis Enrique García; Pascual, Unai (Ecological economics, 2022)
Sustainable farming near tropical forests can buffer ecosystems at risk of biodiversity loss. In mountainous forest frontiers however, many smallholders raise cattle using practices that degrade land, also endangering future livelihoods. Silvopasture, a type of agroforestry, enables cattle farming, biodiversity conservation and can have climate benefits. But its adoption is slow, and ambiguity remains regarding the most relevant predictors for the adoption of agroforestry more broadly. In the context of a pilot silvopastoral project in La Sepultura Biosphere Reserve, we model livelihood diversity as a predictor of both farmers' participation in the project and their adoption of silvopasture (trees grown after a year). We use data collected with a novel token-based approach (n = 104) and account for selection bias. The findings show that livelihood diversity is significantly associated with the two outcomes, but with opposite directions: higher participation and lower adoption levels. Our results provide insight to design and target policies to encourage innovative and sustainable agriculture, especially in contexts of multiple interventions and policy mixes. For example, programmes including economic incentives may consider helping participants overcome different barriers at each stage of the adoption process: in the initial decision to try and during implementation. •Silvopastoral systems combine cattle farming with biodiversity conservation.•We model project participation and silvopasture adoption (commitment) in the forest frontier.•Predictors affect each stage of the process differently.•Livelihood diversity drives participation but interferes with later commitment.•Heterogeneous measures of agroforestry outcomes preclude consensus in the literature.